The implications of streetscape improvement on tourist behaviour at the old quarter of Melaka - Hassim, Nurulhalim (2006)
Melaka is currently applying to be listed as a World Heritage Site. The Old Quarter of Melaka is a part of the conservation area under consideration. In the year 2004, streetscape improvement was completed here. This introduction caused various implications to the behaviour of those utilising this area. In the case of the Old Quarter of Melaka, tourist was one such group. In order to fulfil new tourists need and behaviour, many changes have taken place in this area. Would these changes affect Melaka’s application for the listing? Using quantitative method, this research began by identifying who are the tourists visiting this area, the sites they visited, the activities they participated in, and information and experience they sought. All these factors contribute in determining what was their behaviour within this area. By utilising the Expectation Disconfirmation Method, a clear picture was unveiled about the level of their pre-trip expectation compared to their actual experiences. Their overall satisfaction level was also ascertained. The outcome of this research highlighted the urgency for the need of proper visitor management techniques in order to minimize negative impact and ensure the success of Melaka in becoming a World Heritage Site